Efetividade das intervenções cirúrgicas para o tratamento do dedo em gatilho no adulto: revisão sistemática - Fiorini Junior, Haroldo [UNIFESP] (2016)
Introduction: Trigger finger is characterized by a condition that locks the natural sliding movements of the flexor tendons of the fingers during flexion and extension. Various treatment methods have been used in clinical practice, but there is no consensus regarding which treatment provides the best results. Objective: Verify the effectiveness and safety of different surgical methods for the treatment of trigger finger in adults at any stage of this condition. Method: A systematic review including randomized controlled trials that compared surgical treatment methods with each other or with any other non-surgical intervention was performed. The following databases were searched up to May 2016: Cochrane Musculoskeletal Group Register, Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and LILACS. There were no restrictions on the language of publication. Randomized clinical trials were included which evaluated adults with trigger finger, comparing the surgical treatment methods with each other or with any other non-surgical intervention. The primary outcomes were: resolution of trigger finger, adverse events and hand function. Two authors independently selected the studies, extracted the data and assessed the risk of bias. Where possible, the data were grouped in a meta-analysis using the fixed effect model, with 95% confidence interval. Results: Eleven studies were included, totalling 1.033 participants, with 1.132 trigger fingers. The analysis of the results for resolution were favourable to surgical treatment, when compared with non surgical treatment (223/229 versus 116/175; relative risk (RR) 1,41, 95% CI 1,28 to 1,56; p <0.00001), in the follow-up if six to 42 months. The open surgical treatment had a significantly higher resolution rate than corticosteroid injection, after one application (56/56 versus 28/49; RR 1.74, 95% CI 1:37 to 2:22; p <0.00001), as well as after one or more applications (56/56 vs. 42/49; RR 1.17 95% CI 1:04 to 1:31; p = 0.01), in the follow-up of six months. A favourable significant difference for percutaneous surgery was found in the comparison with the corticosteroid injection, after one (45/45 versus 28/49; RR 1.74, IC of 95% 1.36 to 2.21), as well as after one or more applications (89/92 versus 54/99; RR 1.77, IC of 95% 1.48 to 2.12; I² = 98%), in the follow-up of six to 12 months. There was no significant difference for resolution of trigger finger between treatments with percutaneous or open surgery (198/199 versus 197/198; RR 1.00, IC of 95% 0.98 to 1.03; p = 0.95; I² = 0%) in the follow-up of two to six months, as well as in the comparison between endoscopic or open surgery (114/114 versus 117/117; RR 1.00; IC of 95% 0.98 to 1.02), in the follow-up of three months. There was no significant difference between the comparison groups regarding the occurrence of adverse effects. No study reported complete data on hand function. Conclusion: The open or percutaneous surgical treatments were more effective than the treatment with corticosteroid injection. The percutaneous and endoscopic surgeries had the same effectiveness as open surgery in the treatment of trigger finger. The evidences of this review were obtained from randomized clinical trials of moderate/low methodological quality.